Wide-temperature-range adaptive agm separator and preparation process thereof
Patent Information
- Application Number
- CN202611246447.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-27
AI Technical Summary
[0007]针对现有技术的缺陷与技术空白,本发明提供一种宽温域适配型AGM隔板及其制备工艺,解决传统AGM隔板高低温性能对冲、温域适配窄、高温易失水坍塌、低温内阻大、结构稳定性差的技术问题,实现隔板孔道结构、亲液性能、导通能力随温度无源自适应调控,大幅提升铅酸电池宽温域工作性能与循环寿命
本发明引入无源温感自适应调控机制,有效改善了传统AGM隔板普遍存在的高低温性能对冲问题。本发明打破传统AGM隔板静态结构设计思维,将NIPAM温感微凝胶共价接枝于玻纤基体表面,依托高分子可逆相变特性,可实现低温扩孔降阻、高温缩孔锁液的双向自适应调控效果。该结构能够在低温环境下降低电池内阻,改善电池低温放电容量表现,同时可在高温工况下缓解电解液失水现象,抑制玻纤基体热蠕变与孔隙坍塌情况,提升隔板及电池的高温耐老化性能,改善现有技术的使用局限性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lead-acid battery separator technology, specifically relating to a wide-temperature-range adaptable AGM separator and its preparation process. Background Technology
[0002] Existing commercially available AGM separators are mostly manufactured using a mixture of ultrafine glass fiber and acid-resistant glass fiber. The basic performance of the separator is optimized through methods such as improving fiber ratio, pore structure, and inorganic powder doping modification, making it the mainstream separator material for lead-acid batteries. However, AGM separators prepared using existing technologies are all static structures and static performance systems. Their structure and pore state cannot adaptively adjust with changes in battery operating temperature, resulting in unavoidable technical defects that severely limit the application of lead-acid batteries under extreme operating conditions across a wide temperature range.
[0003] First, traditional AGM separators suffer from a severe conflict between high and low temperature performance. In low-temperature environments (-20℃ to -40℃), the viscosity of the battery electrolyte increases significantly, increasing the resistance to ion migration. Traditional static porous separators have fixed pore conductivity, which cannot adapt to the low-temperature ion transport requirements, resulting in a sharp increase in battery internal resistance, a significant decrease in low-temperature capacity retention, and difficulty in starting discharge. In high-temperature environments (45℃ to 60℃), traditional separators have loose pores and limited liquid retention capacity, leading to rapid evaporation of electrolyte water. At the same time, the glass fiber matrix is prone to thermal creep and pore collapse deformation, causing battery dehydration and drying, increased risk of thermal runaway, severe high-temperature float charge degradation, and a significant reduction in cycle life.
[0004] Secondly, existing modification technologies cannot fundamentally resolve the performance contradictions. Currently, the mainstream modification methods in the industry include fiber ratio optimization, silica / alumina inorganic powder doping, and multilayer glass fiber composite structure design. All of these technologies are passive and static optimizations: inorganic powder modification can improve high-temperature liquid retention and corrosion resistance, but it can clog micropores and increase low-temperature internal resistance; multilayer composite structures can balance room-temperature performance, but they suffer from weak interlayer bonding, easy delamination during thermal cycling, and structural distortion and failure, and still lack temperature response capability.
[0005] Furthermore, existing smart separator technologies are not suitable for the operating conditions of AGM lead-acid batteries. The limited amount of existing temperature-sensitive adaptive modification technologies are only applied to PP / PE organic separators for lithium-ion batteries, employing coating and physical blending modification methods. These methods are only suitable for lithium batteries operating in weakly acidic and alkaline environments, primarily at room temperature. However, lead-acid batteries experience special operating conditions such as strongly acidic electrolytes, oxygen recombination reactions, drastic high and low temperature cycling, and plate extrusion stress. The coating modification methods used for lithium-ion battery temperature-sensitive separators are prone to peeling, swelling, and failure, making them unsuitable for the matrix characteristics of AGM glass fiber separators and the operating system of lead-acid batteries. Therefore, the industry has yet to find a mature, wide-temperature-range adaptive AGM separator solution suitable for lead-acid batteries.
[0006] In summary, the existing technology lacks a temperature-sensitive adaptive AGM separator that can dynamically adjust the pore structure with temperature, balance low-resistance conduction at ultra-low temperatures and liquid-locking anti-collapse at high temperatures, maintain structural stability across the entire temperature range, and adapt to the strong acid conditions of lead-acid batteries. At the same time, there is no matching dedicated manufacturing process, which has become the core technical bottleneck restricting the performance upgrade of wide-temperature-range lead-acid batteries. Summary of the Invention
[0007] To address the shortcomings and gaps in existing technologies, this invention provides a wide-temperature-range adaptable AGM separator and its manufacturing process, solving the technical problems of traditional AGM separators such as performance conflict between high and low temperatures, narrow temperature range adaptability, easy water loss and collapse at high temperatures, high internal resistance at low temperatures, and poor structural stability. It achieves passive adaptive control of the separator's pore structure, hydrophilic properties, and conductivity with temperature, significantly improving the wide-temperature-range performance and cycle life of lead-acid batteries.
[0008] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a wide temperature range adaptable AGM separator, comprising a composite glass fiber matrix and a temperature-sensitive adaptive modification layer covalently grafted onto the surface of the glass fiber matrix; the composite glass fiber matrix is formed by interweaving ultrafine glass fibers and ECR acid-resistant glass fibers; the temperature-sensitive adaptive modification layer is an N-isopropylacrylamide microgel polymer layer, covalently grafted onto the surface of the glass fiber through a low-temperature plasma activation process, without physical coating or additional adhesive layer.
[0009] Furthermore, in the composite glass fiber matrix, the diameter of the ultrafine glass fiber is 0.4 to 0.7 μm, the diameter of the ECR acid-resistant glass fiber is 1.0 to 1.3 μm, and the mass ratio of the two is 7:3. This ratio can take into account both the fine ion transport channels at low temperature and the creep resistance of the structure at high temperature, and balance the flexibility and structural strength of the partition.
[0010] Furthermore, the grafting rate of the temperature-sensitive adaptive modified layer is controlled at 8% to 12% to precisely adapt to the working conditions of lead-acid batteries; the critical phase transition temperature of the temperature-sensitive modified layer is 35°C, corresponding to the critical node between room temperature and high temperature operation of lead-acid batteries.
[0011] Furthermore, the temperature-sensitive adaptive modified layer has reversible temperature-change control characteristics: in the low-temperature range below 35°C, the polymer chain segments expand, increasing the micropore size of the glass fiber, improving the surface hydrophilicity, and reducing the electrolyte transport resistance; in the high-temperature range above 35°C, the polymer chain segments thermally shrink, densifying the microstructure of the glass fiber surface, sealing the electrolyte leakage channels, and inhibiting high-temperature moisture evaporation and matrix thermal creep.
[0012] A manufacturing process for a wide-temperature-range adaptable AGM separator includes the following steps: S1. Precise slurry preparation and dissolution: Take ultrafine glass fiber and ECR acid-resistant glass fiber in proportion, prepare low-concentration glass fiber slurry, and dissolve at low speed until the fibers are evenly dispersed and there is no agglomeration or fiber breakage, so as to obtain a uniform and stable glass fiber slurry.
[0013] S2. Wet forming: The prepared glass fiber slurry is integrally formed by negative pressure adsorption to obtain a partition blank with uniform thickness and regular pore structure.
[0014] S3, Three-stage low-temperature gradient curing: The partition blank is dried by a segmented low-temperature gradient curing process of 80℃ pre-drying, 100℃ shaping drying, and 85℃ constant temperature dehumidification. The moisture is removed slowly in a gradient, which stabilizes the pore structure of the matrix and avoids pore collapse and board warping caused by high-temperature drying.
[0015] S4. Low-temperature plasma surface activation: Argon plasma activation treatment is performed on the solidified and shaped partition to generate high-density hydroxyl and carboxyl active functional groups on the glass fiber surface, providing reliable reaction sites for subsequent covalent grafting of temperature-sensitive microgels.
[0016] S5. Temperature-sensitive microgel covalent grafting modification: The activated separator is immersed in N-isopropylacrylamide microgel modification solution, and a chemical bonding reaction occurs under constant temperature to achieve uniform covalent grafting. After the reaction is completed, the unreacted free components and impurities on the surface of the separator are washed away.
[0017] S6. Secondary constant temperature shaping: The grafted and modified partition is dried and shaped at a constant temperature to eliminate internal stress in the board, stabilize the micro-channels and modified layer structure, and finally obtain a wide temperature range adaptable AGM partition.
[0018] Furthermore, in this preparation process, the specific parameters for the precise dissolution of S1 slurry are as follows: the mass ratio of ultrafine glass fiber to ECR acid-resistant glass fiber is 7:3, the slurry mass concentration is 0.8% to 1.2%, and the low-speed dissolution time is controlled at 15 to 20 minutes.
[0019] Furthermore, in this preparation process, the specific parameters for S2 wet papermaking are as follows: the negative pressure for negative pressure adsorption molding is 0.03 to 0.05 MPa, and the thickness of the partition blank is controlled to be 1.8 to 2.2 mm.
[0020] Furthermore, in this preparation process, the specific parameters for the S3 three-stage low-temperature gradient curing are as follows: the total drying time for the three-stage low-temperature gradient curing is controlled to be 60-80 min.
[0021] Furthermore, in this preparation process, the specific parameters for S4 low-temperature plasma surface activation are as follows: the plasma treatment environment is an argon inert atmosphere, the vacuum degree is 8-12 Pa, the discharge power is 150-200 W, and the activation treatment time is 3-5 min.
[0022] Furthermore, in this preparation process, the specific parameters for the covalent grafting modification of S5 temperature-sensitive microgel are as follows: the mass concentration of the N-isopropylacrylamide microgel modification solution is 5% to 8%, the constant temperature reaction temperature is 40℃, and the reaction time is 25 to 30 min.
[0023] Furthermore, in this preparation process, the specific parameters for the secondary isothermal setting of S6 are as follows: the isothermal drying and setting temperature is 75℃, and the setting time is 30min.
[0024] Beneficial effects Compared with the prior art, the present invention has the following advantages: This invention introduces a passive temperature-sensing adaptive control mechanism, effectively improving the high-low temperature performance conflict problem commonly found in traditional AGM separators. Breaking away from the static structural design of traditional AGM separators, this invention covalently grafts NIPAM temperature-sensing microgels onto the surface of a glass fiber matrix. Leveraging the reversible phase transition properties of polymers, it achieves a bidirectional adaptive control effect of low-temperature pore expansion and resistance reduction, and high-temperature pore shrinkage and electrolyte locking. This structure can reduce battery internal resistance at low temperatures, improve battery low-temperature discharge capacity, and simultaneously alleviate electrolyte water loss under high-temperature conditions, suppressing thermal creep and pore collapse of the glass fiber matrix, enhancing the high-temperature aging resistance of the separator and battery, and overcoming the limitations of existing technologies.
[0025] The modified structure of this invention exhibits excellent stability, effectively avoiding many shortcomings of traditional modification processes. This invention employs a low-temperature plasma-activated covalent grafting process, enabling the temperature-sensitive modified layer to form a stable chemical bond with the glass fiber matrix. Unlike traditional modification methods such as coating, physical doping, and multilayer physical composites, this method is less prone to problems such as modified layer detachment, polymer swelling, and structural delamination failure. Under complex operating conditions such as immersion in strong acid electrolytes, wide-temperature alternating hot and cold cycles, and continuous plate compression in lead-acid batteries, the structure and function of the modified layer remain relatively stable, which is beneficial for improving the overall cycle life of lead-acid batteries. Detailed Implementation
[0026] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0027] Example 1 A manufacturing process for a wide-temperature-range adaptable AGM separator includes the following steps: S1. Slurry preparation and descaling: Select 0.5μm ultrafine glass fiber and 1.1μm ECR acid-resistant glass fiber, mix them at a mass ratio of 7:3, prepare a deionized water slurry with a mass concentration of 1.0%, and descale at low speed for 18 minutes to obtain agglomerated and uniform glass fiber slurry. S2. Forming: Forming is carried out under a constant negative pressure of 0.04MPa, and the thickness of the partition blank is controlled at 2.0mm. S3. Low-temperature gradient curing: Pre-drying at 80℃ for 25 minutes, shaping and drying at 100℃ for 35 minutes, and constant temperature dehumidification at 85℃ for 10 minutes, with a total drying time of 70 minutes. Segmented gradient drying stabilizes the pore structure. S4. Plasma activation: Under an argon atmosphere, with a vacuum of 10 Pa and a discharge power of 180 W, the activation treatment lasted for 4 minutes to activate the functional groups on the glass fiber surface. S5. Covalent grafting modification: Prepare a 6% N-isopropylacrylamide microgel aqueous solution, wet it at 40℃ for 28 min, and rinse with deionized water to remove free impurities. Example 2 A manufacturing process for a wide-temperature-range adaptable AGM separator includes the following steps: S1. Slurry preparation and desizing: Select 0.4μm ultrafine glass fiber and 1.0μm ECR acid-resistant glass fiber, mix them at a mass ratio of 7:3, prepare a deionized water slurry with a mass concentration of 0.8%, and desizing at low speed for 15 minutes to obtain a uniform glass fiber slurry. S2. Forming: Forming is carried out under constant negative pressure of 0.03MPa, and the thickness of the partition blank is controlled at 1.8mm. S3, Low-temperature gradient curing: Pre-drying at 80℃ for 20 min, shaping and drying at 100℃ for 30 min, constant temperature dehumidification at 85℃ for 10 min, total drying time 60 min; S4. Plasma activation: Under an argon atmosphere, with a vacuum of 8 Pa and a discharge power of 150 W, activation treatment is carried out for 3 min. S5. Covalent grafting modification: Prepare a 5% N-isopropylacrylamide microgel aqueous solution, wet it at 40℃ for 25 min, and rinse with deionized water to remove free impurities. S6. Secondary shaping: Dry and shape at 75℃ for 30 minutes to obtain the finished partition, with a modified layer grafting rate of 8%.
[0028] Example 3 A manufacturing process for a wide-temperature-range adaptable AGM separator includes the following steps: S1. Slurry preparation and descaling: Select 0.7μm ultrafine glass fiber and 1.3μm ECR acid-resistant glass fiber, mix them at a mass ratio of 7:3, prepare a deionized water slurry with a mass concentration of 1.2%, and descale at low speed for 20 minutes to obtain a uniform glass fiber slurry. S2. Forming: Forming is carried out under a constant negative pressure of 0.05MPa, and the thickness of the partition blank is controlled at 2.2mm. S3, Low-temperature gradient curing: Pre-drying at 80℃ for 30 min, shaping and drying at 100℃ for 40 min, constant temperature dehumidification at 85℃ for 10 min, total drying time 80 min; S4. Plasma activation: Under an argon atmosphere, with a vacuum of 12 Pa and a discharge power of 200 W, activation treatment was carried out for 5 min. S5. Covalent grafting modification: Prepare an 8% N-isopropylacrylamide microgel aqueous solution, wet it at 40℃ for 30 min, and rinse with deionized water to remove free impurities. S6. Secondary shaping: Dry and shape at 75℃ for 30 minutes to obtain the finished partition, with a modified layer grafting rate of 12%.
[0029] Comparative Example 1 This comparative example uses the same glass fiber raw materials, proportions, papermaking, and three-stage low-temperature gradient curing parameters as Example 1, without plasma activation and temperature-sensitive microgel grafting modification. It is used to verify the effect of the temperature-sensitive modified layer on improving the wide-temperature-range performance of the separator. The specific preparation steps are as follows: S1. Slurry preparation and descaling: Select 0.5μm ultrafine glass fiber and 1.1μm ECR acid-resistant glass fiber, mix them at a mass ratio of 7:3, prepare a deionized water slurry with a mass concentration of 1.0%, and descale at low speed for 18 minutes to obtain agglomerated and uniform glass fiber slurry. S2. Forming: Forming is carried out under a constant negative pressure of 0.04MPa, and the thickness of the partition blank is controlled at 2.0mm. S3, Low-temperature gradient curing: sequentially pre-drying at 80℃ for 25 min, shaping and drying at 100℃ for 35 min, and constant temperature dehumidification at 85℃ for 10 min, with a total drying time of 70 min; S4. Secondary shaping: The cured partition is directly placed at 75℃ for drying and shaping for 30 minutes to obtain a pure glass fiber AGM partition without temperature-sensitive modification.
[0030] Comparative Example 2 This comparative example uses the same raw materials, proportions, papermaking, and modification parameters as Example 1, only replacing the curing process. It is used to verify the optimization effect of the three-stage low-temperature gradient curing process of the present invention on the performance of the separator. The specific preparation steps are as follows: S1. Slurry preparation and desizing: Select 0.5μm ultrafine glass fiber and 1.1μm ECR acid-resistant glass fiber, mix them at a mass ratio of 7:3, prepare a deionized water slurry with a mass concentration of 1.0%, and desizing at low speed for 18 minutes to obtain a uniform glass fiber slurry. S2. Forming: Forming is carried out under a constant negative pressure of 0.04MPa, and the thickness of the partition blank is controlled at 2.0mm. S3, Traditional High-Temperature Curing: The molded preform is placed in a high-temperature environment of 120℃ and continuously dried for 70 minutes to complete the curing of the preform; S4. Plasma activation: Under an argon atmosphere, with a vacuum of 10 Pa and a discharge power of 180 W, activation treatment was carried out for 4 min. S5. Covalent grafting modification: Prepare a 6% N-isopropylacrylamide microgel aqueous solution, wet it at 40℃ for 28 min, and rinse with deionized water to remove free impurities. S6. Secondary shaping: Dry and shape at 75℃ for 30 minutes to obtain the traditional high-temperature curing temperature-sensitive modified AGM partition.
[0031] Comparative Example 3 This comparative example is a mainstream commercially available high-temperature resistant AGM separator, which uses an inorganic powder doping modification process and lacks temperature-sensitive adaptive control capability. It serves as a standard benchmark product on the market to highlight the technical advantages of the temperature-sensitive adaptive modification of this invention. The specific preparation steps are as follows: S1. Slurry preparation and loosening: Select 0.5μm ultrafine glass fiber and 1.1μm ECR acid-resistant glass fiber, mix them at a mass ratio of 7:3, add 5% of the total fiber mass of nano silica powder, prepare a deionized water slurry with a mass concentration of 1.0%, and loosen it at low speed for 18 minutes using frequency conversion. S2. Forming: Forming is carried out under a constant negative pressure of 0.04MPa, and the thickness of the partition blank is controlled at 2.0mm. S3. High-temperature curing: Curing is completed by a one-time high-temperature drying at 120℃ for 70 minutes; S4. Secondary shaping: Dry and shape at 75℃ for 30 minutes to obtain conventional inorganic modified AGM separator.
[0032] S3. High-temperature curing: Curing is completed by a one-time high-temperature drying at 120℃ for 70 minutes; The separators of each embodiment and the comparative embodiment were uniformly assembled into a 12V lead-acid battery of the same specification. Under the same environment and uniform testing standards, low-temperature discharge, high-temperature float charge aging, and wide-temperature alternating cycle were carried out. The performance data are summarized in the table below: Table 1. Summary of performance test results for each embodiment and comparative example of the present invention.
[0033] Performance test results comparison and analysis As shown in the test data above, the multiple gradient embodiments of this invention exhibit stable performance. The process parameters and material ratio ranges defined in the claims demonstrate good feasibility and adaptability, and all parameter combinations within these ranges can produce AGM separators with excellent performance over a wide temperature range. Compared to the comparative examples, this invention achieves a good technical synergy through temperature-sensitive adaptive covalent grafting modification combined with a three-stage low-temperature gradient curing process, effectively improving the shortcomings of traditional AGM separators in terms of high and low temperature performance conflict. At low temperatures, it can effectively reduce battery internal resistance and increase low-temperature discharge capacity; at high temperatures, it can suppress electrolyte water loss and substrate aging deformation, reducing capacity decay; simultaneously, it can significantly reduce performance loss under wide-temperature alternating cycles, and exhibits good structural stability under long-term operating conditions, demonstrating significant technical advantages compared to existing conventional modification processes.
[0034] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A wide-temperature-range adaptable AGM separator, characterized in that: The product includes a composite glass fiber matrix and a temperature-sensitive adaptive modification layer covalently grafted onto the surface of the composite glass fiber matrix. The composite glass fiber matrix is formed by interweaving ultrafine glass fibers and ECR acid-resistant glass fibers. The temperature-sensitive adaptive modification layer is an N-isopropylacrylamide microgel polymer layer, which is covalently grafted onto the glass fiber surface through a low-temperature plasma activation process, without any physical coating or additional adhesive layer.
2. The temperature-sensitive adaptive wide-temperature-range AGM separator according to claim 1, characterized in that: The ultrafine glass fiber has a diameter of 0.4–0.7 μm, and the ECR acid-resistant glass fiber has a diameter of 1.0–1.3 μm, with a mass ratio of 7:
3.
3. The temperature-sensitive adaptive wide-temperature-range AGM separator according to claim 1, characterized in that: The grafting rate of the temperature-sensitive adaptive modified layer is 8% to 12%, and the critical phase transition temperature is 35°C.
4. The temperature-sensitive adaptive wide-temperature-range AGM separator according to claim 1, characterized in that: The temperature-sensitive adaptive modified layer has reversible temperature-controlled characteristics: when the temperature is below 35°C, the polymer chain segments expand, increasing the micropore size of the glass fiber and improving the surface hydrophilicity; when the temperature is above 35°C, the polymer chain segments thermally shrink, densifying the surface structure of the glass fiber and sealing the electrolyte leakage channels.
5. A manufacturing process for a wide-temperature-range adaptable AGM separator, characterized in that, Includes the following steps: S1. Precise slurry preparation and dispersing: Take ultrafine glass fiber and ECR acid-resistant glass fiber in proportion, prepare low-concentration glass fiber slurry, and disperse at low speed until the fibers are evenly dispersed; S2. Wet paper forming: The glass fiber slurry is formed by negative pressure adsorption to obtain the partition blank; S3, Three-stage low-temperature gradient curing: The partition blank is dried using a segmented low-temperature gradient curing process of 80℃ pre-drying, 100℃ shaping drying, and 85℃ constant temperature dehumidification. S4. Low-temperature plasma surface activation: Argon plasma activation treatment is performed on the cured partition to generate active functional groups on the glass fiber surface. S5. Temperature-sensitive microgel covalent grafting modification: The activated partition is immersed in N-isopropylacrylamide microgel modification solution, and covalent grafting is achieved by constant temperature reaction. Free components are removed by rinsing. S6. Secondary constant temperature shaping: The modified partition is dried and shaped at a constant temperature to obtain the finished partition.
6. The manufacturing process of a temperature-sensitive adaptive wide-temperature-range AGM separator according to claim 5, characterized in that: In step S1, the slurry mass concentration is 0.8% to 1.2%, and the disintegration time is 15 to 20 minutes.
7. The manufacturing process of a temperature-sensitive adaptive wide-temperature-range AGM separator according to claim 5, characterized in that: In step S2, the forming negative pressure is 0.03 to 0.05 MPa, and the forming thickness of the partition is 1.8 to 2.2 mm.
8. The manufacturing process of a temperature-sensitive adaptive wide-temperature-range AGM separator according to claim 5, characterized in that: In step S3, the total drying time is controlled to be 60-80 minutes.
9. The manufacturing process of a temperature-sensitive adaptive wide-temperature-range AGM separator according to claim 5, characterized in that: In step S4, the plasma treatment vacuum degree is 8-12 Pa, the discharge power is 150-200 W, and the activation time is 3-5 min.
10. The manufacturing process of a temperature-sensitive adaptive wide-temperature-range AGM separator according to claim 5, characterized in that: In step S5, the mass concentration of the modified solution is 5%–8%, the reaction temperature is 40℃, and the reaction time is 25–30 min; in step S6, the setting temperature is 75℃, and the setting time is 30 min.